Synthesis and Antimicrobial Activity of Some New 1, 4-Benzothiazine Containing Thiosemicarbazides and 1, 3, 4-Oxadiazole Derivatives - Bhikan J Khairnar; Rahul S. Salunke; Premchand B. Patil; Sanjay A . Patil; Rajeshwar J . Kapade; Pravin S. Girase; Bhata R. Chaudhari (E-Journal of Chemistry)
A series of novel 3- methyl-7-substituted-4H,4-benzothiazine-2-carbohydrazide (3a-e) and corresponding thiosemicarbazides (4-a-q); 2-[3-methyl-7-substituted- 4H -1, 4-benzothiazine-2-yl]-N-(aryl) hydrazine carbothiamide have been synthesized. The thiosemicarbazide when cyclized with iodine via intramolecular cyclisation gave benzothiazonyl oxadiazoles (5-a-q); 5-(3-methyl -7-substitued-4H- 1,4-benzothiazin-2-yl)- N —aryl- 1,3,4- oxadiazol -2-amine and the compounds were tested for antibacterial and antifungal activities against different microorganisms.